Development of robot kit for visually impaired - Chee, Fang Lit (2017)
Visual impairment is the loss of the ability to see either gradually or totally lost sight, this situation also call blind. People who suffer with this lost are called visually impaired. They are experienced many inconvenience and one of them is their mobility is totally affected where they camot travel like ordinary people because their visual information is less compare with other. Therefore, a guidance robot which can guide the visually impaired away from obstacle and wall is required. With this avoidance, visually impaired can less concern about their defective vision because they can follow the guidance path of the robot. The robot is equipped with three ultrasonic sensors which is function as the "eyes" of visually impaired for gather the distance information in an area in front them. All the distance information is used as condition to alter the ratio of pulse width modulation applied to each motor of the robot. Thus, the speed of the wheels is based on the condition of environment. To test the functionality of the obstacle avoidance algorithm, the guidance robot is tested in three different situations. The overall success rate is around 83.33 percent. Apart from these, biomaterial is attempted to use to construct the body structure of the robot where the shape of the robot's body structure is successfully fabricated out.